2011
DOI: 10.1159/000330448
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum S100A12 and sRAGE Associated with Improvement of the PaO<sub>2</sub>/FiO<sub>2</sub> Ratio following PMX-DHP Therapy for Postoperative Septic Shock

Abstract: Background: Endotoxin (Et) adsorption therapy with a column of polymyxin B-immobilized fibers (PMX) is effective in improving the partial pressure of arterial oxygen/fraction of inspired oxygen ratio (PaO2/FiO2 ratio) and increasing mean arterial blood pressure (MAP) in sepsis. S100A12 and soluble receptor for advanced glycation end product (sRAGE) are useful as early markers of acute lung injury. Purpose: To investigate the effect of improving the PaO2/FiO2 ratio by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…We found that elevated sputum levels may be useful to assess eosinophilic asthma [284]. High concentrations of MMP-7, ICAM-1, IL-8, VCAM-1, and S100A12 predicted poor overall survival of patients with idiopathic pulmonary fibrosis [352] and S100A12 is useful as an early marker of acute, early-stage lung injury in patients with sepsis [353,354]. …”
Section: S100 Proteins As Disease Markersmentioning
confidence: 99%
“…We found that elevated sputum levels may be useful to assess eosinophilic asthma [284]. High concentrations of MMP-7, ICAM-1, IL-8, VCAM-1, and S100A12 predicted poor overall survival of patients with idiopathic pulmonary fibrosis [352] and S100A12 is useful as an early marker of acute, early-stage lung injury in patients with sepsis [353,354]. …”
Section: S100 Proteins As Disease Markersmentioning
confidence: 99%
“…We recorded the positive dynamics of the oxygenation index while assessing oxygenic pulmonary function in the context of PMX hemoperfusion. In our opinion, the impact of this hemocorrection method on pulmonary function is based on the reduction in the endothelial permeability of pulmonary vessels, suppression of nitric oxide production, and decrease in monocyte activity and sequestration and aggressive molecules of the inflammatory cascade [13, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of hemoadsorption treatment in this case could probably be due to multiple mechanism of immunomodulation, not only endotoxin removal. Notably PMX-DHP reduces the concentration of pro-inflammatory and anti-inflammatory cytokines [8], high mobility group box protein 1 (HMGB-1) [9], and the receptor for advanced glycation end-products [10] decreasing in the excessive systemic host inflammatory response to infection.…”
Section: Discussionmentioning
confidence: 99%